Metal‐Free Electrocatalyst for Oxygen Reduction: Synthesis‐Controlled Density of Catalytic Centers and Impact on ORR. Issue 12 (21st November 2014) - Cong, Kun; Ritter, Marcel; Stumpf, Steffi; Schröter, Bernd; Schubert, Ulrich S.; Ignaszak, Anna
Abstract This work demonstrates a rapid and scalable route for the preparation of N‐doped carbon spheres of 80–120 nm via pyrolysis of polypyrrole as the only carbon and nitrogen source. The resulting porous catalyst has a nitrogen doping level of 6–8 at%. Electrochemical studies show that N‐doped C is very active toward oxygen reduction in alkaline electrolyte and the mechanism of ORR process is controlled by the surface concentration of catalytic active sites that promote either a direct four‐electron or two‐electron process. An interesting observation is that we can generate precursors for the N‐doped carbon with desirable particle size, shape and with the preferential structure (linear polypyrrole from the αα coupling during slow polymerization or cross‐linked polypyrrole from αβ coupling during fast polymerization) that promotes the formation of favorable catalytic sites for O2 reduction. The XPS analysis in conjunction with RDE voltammetry highlights the effect of polymer precursor synthesis on the chemical structure and a resulting electrochemical activity of the N‐doped carbon materials.